2017
DOI: 10.1080/19382014.2017.1356963
|View full text |Cite
|
Sign up to set email alerts
|

Vascular-derived connective tissue growth factor (Ctgf) is critical for pregnancy-induced β cell hyperplasia in adult mice

Abstract: During pregnancy, maternal β cells undergo compensatory changes including hypertrophy, hyperplasia, and increased glucose-stimulated insulin secretion (GSIS). Failure of these adaptations to occur can result in gestational diabetes mellitus. The secreted protein, Connective tissue growth factor (Ctgf), is critical for normal β cell development and promotes regeneration after partial β cell ablation. During embryogenesis, Ctgf is expressed in pancreatic ducts, vasculature, and β cells. In the adult pancreas, Ct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…It suggests that there is a disturbance in the ratio between connective and muscle tissues, which are characteristic for UCTD. Similar changes in the form of reduction of the collagen amount and increased mass of muscle tissue are observed in a case of cervical insufficiency [3,11].…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…It suggests that there is a disturbance in the ratio between connective and muscle tissues, which are characteristic for UCTD. Similar changes in the form of reduction of the collagen amount and increased mass of muscle tissue are observed in a case of cervical insufficiency [3,11].…”
Section: Introductionsupporting
confidence: 71%
“…Cervical insufficiency (CI) is one of the leading reasons of extremely early and early preterm deliveries. Clinically CI happens at 22-28 weeks of pregnancy leading to premature deliveries and such newborns have indicators of perinatal morbidity and mortality [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both these genes are expressed only in late embryonic beta cell development and emerging islets (Arnaud-Dabernat et al 2007, Crawford et al 2009). Particularly, Ctgf inactivation during embryogenesis caused decreased insulin-positive cells (Crawford et al 2009), while Ctgf haploinsufficiency mice had decreased beta cell proliferation during pregnancy (Pasek et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Current published data addressing CCNs in pancreatic islets, and specifically in pancreatic beta-cells, suggests multiple roles of the CCNs in differing stages of pancreatic beta-cell development and pathology. While the original studies of CCN2 homozygous global gene knockout did not find an overt pancreatic abnormality (Ivkovic et al 2003), more recent publications have interrogated and found an important role for CCN2 in endocrine pancreatic development prenatally, indicating it is required for beta-cell proliferation, differentiation, and islet morphogenesis during development (Charrier and Brigstock 2013), (Crawford et al 2009), as well as beta-cell function gestationally (Pasek et al 2016), (Pasek et al 2017). CCN2 also mediated adult beta-cell proliferation in the setting of a murine model of partial beta-cell ablation in a macrophage dependent manner, suggesting CCN2 may have a role in preventing persistent adult islet dysfunction linked to inflammation (Riley et al 2015).…”
Section: Ccns In Pancreatic Endocrine Function Linking To Insulin Secmentioning
confidence: 99%